2013
DOI: 10.4161/auto.27162
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy facilitates TLR4- and TLR3-triggered migration and invasion of lung cancer cells through the promotion of TRAF6 ubiquitination

Abstract: (2014) Autophagy facilitates TLR4-and TLR3-triggered migration and invasion of lung cancer cells through the promotion of TRAF6 ubiquitination, Autophagy, 10:2, 257-268,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(204 citation statements)
references
References 50 publications
7
190
0
Order By: Relevance
“…Knockdown of ATG7 strongly enhanced the apoptosis induced by various anticancer agents including tyrosine kinase inhibitors [18][19][20]. Recent studies showed that autophagy may promote carcinoma cell invasion and correlate with poor prognosis in cholangiocarcinoma [21,22]. In this study, we found that blockage of autophagy by downregulation of ATG7 or MARCH7 expression led to the inhibition of TGF-β induced cellular migration and invasion.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 53%
“…Knockdown of ATG7 strongly enhanced the apoptosis induced by various anticancer agents including tyrosine kinase inhibitors [18][19][20]. Recent studies showed that autophagy may promote carcinoma cell invasion and correlate with poor prognosis in cholangiocarcinoma [21,22]. In this study, we found that blockage of autophagy by downregulation of ATG7 or MARCH7 expression led to the inhibition of TGF-β induced cellular migration and invasion.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 53%
“…Regarding ovarian tumors, it has been suggested that TLR2, TLR3, TLR4 and TLR5 have high levels of expression in normal ovarian epithelium and epithelial ovarian neoplasms (7). It was also revealed that TLR4 has a high expression level in ovarian granular cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…TLRs are usually expressed in cancer cells and are responsible for the regulation of autophagy as well as several immune responses [11]. Autophagy triggered by TLR3 and TLR4 was shown to contribute to the progression of lung cancer [12]. However, several studies have suggested that TLR activation enhances the survival, proliferation, and metastasis of cancer cells [12,16,17,18,19].…”
Section: Autophagy As An Innate Immune Response Against Cancermentioning
confidence: 99%
“…However, several studies have suggested that TLR activation enhances the survival, proliferation, and metastasis of cancer cells [12,16,17,18,19]. Furthermore, TLRs trigger the release of proinflammatory cytokines, chemokines, and immunosuppressive factors, leading to immune evasion and enhanced cancer cell resistance [12,19].…”
Section: Autophagy As An Innate Immune Response Against Cancermentioning
confidence: 99%
See 1 more Smart Citation